Cypermethrin induces apoptosis of Sertoli cells through the endoplasmic reticulum pathway. (July 2022) - Shen, Junyu; Wang, Lushan; Wang, Xuxu; Xie, Jiafei; Yao, Tingting; Yu, Yue; Wang, Qi; Ding, Zhen; Zhang, Jinpeng; Zhang, Meirong; Xu, Lichun
Cypermethrin, an extensively used pyrethroid pesticide, is regarded as one of many endocrine-disrupting chemicals (EDCs) with anti-androgenic activity to damage male reproductive systems. We previously found cypermethrin-induced apoptosis in mouse Sertoli cells TM4. We hypothesized cypermethrin-induced TM4 apoptosis by the endoplasmic reticulum (ER) pathway. This study aimed to explore the roles of the ER pathway in cypermethrin-induced apoptosis in TM4 cells. The cells were treated with cypermethrin for 24 h at various concentrations (0 µM, 10 µM, 20 µM, 40 µM, and 80 µM). Flow cytometry was used to test for apoptosis. Western blot was used to test protein expressions in the ER stress pathway. The results showed that the apoptosis rate of TM4 cells increased with increased concentrations of cypermethrin, and a significant difference was detected in the 80-μM group. The protein expressions of glucose-regulated protein 78 (GRP78), protein kinase R (PKR)-like ER kinase (PERK), p-PERK, α subunit of eukaryotic initiation factor (eIF2α), p-eIF2α, activating transcription factor 4 (ATF4), C/EBP homologous protein (CHOP), caspase-12, caspase-9, and caspase-3 increased with increased concentrations of cypermethrin. The results suggested cypermethrin-induced apoptosis in TM4 cells regulated by the ER pathway involving PERK-eIF2α-ATF4-CHOP. The study provides a new insight into cypermethrin-induced apoptosis in Sertoli cells.